2023
DOI: 10.1021/acs.cgd.2c01142
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Computational Analysis of the Solid-Form Landscape of Three Structurally Related Imidazolidine-2,4-dione Active Pharmaceutical Ingredients: Nitrofurantoin, Furazidin, and Dantrolene

Abstract: We present a crystallographic and computational study of three hydantoin-based active pharmaceutical ingre-dients�nitrofurantoin, furazidin, and dantrolene�aimed at identifying factors resulting in different propensities of these compounds to form polymorphs, hydrates, solvates, and solvatehydrates. This study is a continuation of our research toward understanding how small structural differences in closely related compounds affect their propensity to form different crystal phases, as all three compounds conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Identical procedure as in our previous studies were used for the structure determination 32,39 and is given in the Supporting Information.…”
Section: Crystal Structure Determinationmentioning
confidence: 99%
“…Identical procedure as in our previous studies were used for the structure determination 32,39 and is given in the Supporting Information.…”
Section: Crystal Structure Determinationmentioning
confidence: 99%
“…The number of solvates formed by a compound can be significantly different, as for some compounds no solvate has ever been observed, whereas for others, solvate is obtained in crystallization from essentially any solvent, with dozens (for example, for olanzapine , and axitinib , ) or even more than 100 (for sulfathiazole) solvates reported. Our previous studies have shown that identification of factors leading to different propensities of structurally similar compounds to form solvates and solvent selection criteria requires detailed crystallographic and computational analyses. In general, solvate formation is determined by energetic aspects: the energy difference between the two-component structure and two pure components allows the assessment of the formation likelihood of the respective phase, if its crystal structure is known or can be computationally predicted, as demonstrated for cocrystals and solvates. , Additionally, the entropy penalty associated with the transfer of solvent from the liquid to solid state should be considered for solvates …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in solvate-hydrates, a more efficient hydrogen bonding network between the host and the solvent molecules can be formed, with organic solvent molecules filling the cavities. Furthermore, the formation of solvate-hydrates is particularly favored by solvents that can form a hydrogen bond with the water. , Nevertheless, in the literature, there is a limited number of papers focusing on solvate-hydrates and their formation, and in most cases, solvate-hydrates are analyzed just as one of the solvated forms of the studied compound. Although there are no essential differences in the formation mechanism of both types of solvated phases, the observation that some molecules form numerous solvate-hydrates, whereas some prolific solvate formers do not form any, requires investigation of the driving force of the solvate-hydrate formation.…”
Section: Introductionmentioning
confidence: 99%
“…Solvate hydrates are mostly observed for prolific formers of solvated phases, for example, bosutinib and olanzapine, , and are usually formed with highly polar solvents . Among other compounds of pharmaceutical interest, nevirapine, atorvastatin calcium, cholic acid, , deoxycholic acid, , furazidin, , and dantrolene have structurally characterized solvate-hydrates. The size and shape of all of these molecules, except for furazidin and dantrolene, prevent efficient packing, resulting in formation of structures with cavities, and/or allow to achieve efficient hydrogen bonding only in structures with reduced packing efficiency.…”
Section: Introductionmentioning
confidence: 99%